TELUK CENGAL: LOKASI PELABUHAN SRIWIJAYA? - Nurhadi Rangkuti (Berkala Arkeologi, 2017)
Archaeological researches in southeast coast of Sumatra find archaeological prove of Srivijaya era (7-13 AD). Settlement sites located along tidal swamp rivers near shoreline. Srivijaya communities lived on house on stilts from wood on the wetlands. The artifacts came from aboard, eg. Chinese ceramics, beads from India and glasses from Persian found with local artifacts. Also found boats of Southeast Asia tradition use sewn plank and lashed-lug technique. These artifacts represent maritime activities in southeast coast of Sumatra. Estimated southeast coast of Sumatra, which facing Strait of Bangka, is an archaeological settlement area of Srivijaya and also pre Srivijaya periods. This one have the harbour and the port. This paper tried to identify one of the archaeological settlement area which estimated as an entreport of Srivijaya period. This area located in Bay of Cengal, District of Ogan Komering Ilir, Province of South Sumatra. Remains of activity area concentrated in Lumpur River basin and empties into Java Sea. Identification an archaeological settlement area in Bay of Cengal based on archeological data analysis, textual and maps resources, environment and position of Bay of Cengal in global maritime networks of Srivijaya.